(S,S)-Diiodido{3,3′-methylenebis[1-(1-hydroxy-4-methylpentan-2-yl)imidazol-2-ylene]}palladium(II) ethanol monosolvate - Ping Liao; Yanping Wang; Li Zhong; Jinwei Yuan; Liangru Yang (IUCrData, 2025)
The structure of the title solvated bis-N-heterocyclic carbene palladium(II) complex, [PdI2(C19H32N4O2)2·C2H6O, exhibits a slightly distorted square-planar coordination at the palladium(II) atom, with the six-membered chelate ring adopting a boat conformation. One disordered ethanol solvent molecule was co-crystallized. There are intermolecular O—H...O hydrogen bonds in the structure. The chiral centers of the precursor imidazolium salt was preserved during the metalation process.